Prophylactic Central Neck Dissection for cN1b Papillary Thyroid Carcinoma: A Systematic Review and Meta-Analysis - Yan, Xing Q.; Zhang, Zhen Z.; Yu, Wen J.; Ma, Zhao S.; Chen, Min L.; Xie, Bo J. (Frontiers in Oncology, 2022)
Background. The value of prophylactic central neck dissection (PCND) for papillary thyroid carcinoma (PTC) with clinically evident lateral cervical lymph node metastases (cN1b) remains unclear. Therefore, a systematic review and meta-analysis was conducted to assess the efficacy and safety of PCND. Methods. A comprehensive systematic search was conducted on PubMed, Web of Science, Cochrane library and Embase databases to identify eligible studies. The primary outcomes were the locoregional recurrence (LRR) and complications between PTC patients undergoing total thyroidectomy (TT) and lateral neck dissection (LND) and those undergoing TT and LND combining with PCND. Results. We included 4 retrospective cohort studies, which comprised 483 PTC patients. There was no statistically significant difference in the central neck recurrence (CNR) (10.2% vs. 3.8%, relative risk (RR), = 1.82; 95% CI 0.90–3.67; P = 0.09), lateral neck recurrence (LNR) (5.1% vs. 7.7%, RR = 0.47; 95% CI 0.13–1.74; P = 0.26), and overall recurrence (OR) (18.9% vs. 16.9%, RR = 0.77; 95% CI 0.34–1.76; P = 0.54), between LND+PCND group and LND group. Simultaneously, PCND increased the risk of permanent hypoparathyroidism (11.4% vs. 4.5%, RR = 2.70, 95% CI 1.05–6.94; P = 0.04) and overall complications (17.0% vs. 5.3%, RR = 3.28; 95% CI 1.37–7.86; P = 0.008). Conclusions. This meta-analysis showed that PCND did not have any advantage in preventing LRR for cN1b PTC. Meanwhile, PCND may result in the increased rate of surgical complications. However, the current evidence is limited and more clinical trials are still needed to further clarify the true role of PCND.